Application of Positive Mode Atmospheric Chemical Ionisation to Distinguish Epimeric Oleanolic and Ursolic Acids. Issue 3 (June 2015) - Townley, Chloe; Brettell, Rhea C.; Bowen, Richard D.; Gallagher, Richard T.; Martin, William H.C.
A new and more reliable method is reported for distinguishing the equatorial and axial epimers of oleanolic and ursolic acids and related triterpenoids based primarily on the relative abundance of the [M + H] + and [M + H – H2 O] + signals in their positive mode atmospheric pressure chemical ionisation mass spectra. The rate of elimination of water, which is the principal primary fragmentation of protonated oleanolic and ursolic acids, depends systematically on the stereochemistry of the hydroxyl group in the 3 position. For the β-epimer, in which the 3-hydroxyl substituent is in an equatorial position, [M + H – H2 O] + is the base peak. In contrast, for the α -epimer, where the 3-hydroxyl group is axial, [M + H] + is the base peak. This trend, which is general for a range of derivatives of oleanolic and ursolic acids, including the corresponding methyl esters, allows epimeric triterpenoids in these series to be securely differentiated. Confirmatory information is available from the collision-induced dissociation of the [M + H – H2 O] + primary fragment ions, which follow different pathways for the species derived from axial and equatorial epimers of oleanolic and ursolic acids. These two pieces of independent spectral information permit the stereochemistry of epimeric oleanolic and ursolic acids (and selected derivatives) to be assigned with confidence without relying either on chromatographic retention times or referring to the spectra or other properties of authentic samples of these triterpenoids.